2013
DOI: 10.3109/07420528.2013.842575
|View full text |Cite
|
Sign up to set email alerts
|

Bedtime misalignment and progression of breast cancer

Abstract: Disruption of circadian rhythms, which frequently occurs during night shift work, may be associated with cancer progression. The effect of chronotype (preference for behaviors such as sleep, work, or exercise to occur at particular times of day, with an associated difference in circadian physiology) and alignment of bedtime (preferred vs. habitual), however, have not yet been studied in the context of cancer progression in women with breast cancer. Chronotype and alignment of actual bedtime with preferred chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 41 publications
(57 reference statements)
0
35
0
Order By: Relevance
“…Hahm et al [26] showed that disruption of the circadian rhythm, such as by performing night shift work, might have an association with the progression of breast cancer. Exercise also acts as a regulator on the circadian rhythm and sleep; therefore regular exercise might hypothetically have an indirect effect on preventing the progression of breast cancer.…”
Section: Possible Mechanisms Of Exercisementioning
confidence: 99%
“…Hahm et al [26] showed that disruption of the circadian rhythm, such as by performing night shift work, might have an association with the progression of breast cancer. Exercise also acts as a regulator on the circadian rhythm and sleep; therefore regular exercise might hypothetically have an indirect effect on preventing the progression of breast cancer.…”
Section: Possible Mechanisms Of Exercisementioning
confidence: 99%
“…Results suppor ng the data from mouse models were obtained in human studies as well. Specifically, chronic bed me misalignment was found to be associated with faster tumour progression in pa ents with breast cancer [35]. Tumour progression was also accelerated in mice subjected to experimental condi ons imita ng chronic jet lag [225].…”
Section: Genotype-phenotype Correlations For Mutations and Polymorphimentioning
confidence: 80%
“…Circadian misalignment may be associated with increased risk for development of insulin resistance (metabolic syndrome, diabetes type 2) [28]; various cancers (breast cancer, prostate cancer, colorectal cancer, and others) [29][30][31]; arterial hypertension; cardiac arrhythmia [32][33][34] in other words, many of the diseases of middle and advanced age'. When the cancer had already developed, chronic disrup on of the circadian rhythms may some mes accelerate its progression and/or increase the risk for metastasising [30,35] (for details, see below).…”
mentioning
confidence: 99%
“…Epidemiological studies indicate that breast cancer risk is significantly elevated in industrialized societies and that this risk increases as countries become more westernized. Misalignment of bedtime on a daily basis, which is an indication of social jetlag and circadian disruption, is associated with more rapid breast cancer development (121). Nighttime light levels also codistribute with breast cancer incidents (122).…”
Section: Inflammatory Disorders and Cancermentioning
confidence: 99%